Gram‐Scale Synthesis, Isolation and Characterisation of Sodium Organometallics: nBuNa and NaTMP. Issue 8 (29th July 2022) - Tortajada, Andreu; Anderson, David E.; Hevia, Eva
Abstract: Organolithium compounds represent one of the most widely utilised commodity reagents in synthetic chemistry. However, their analogues with the heavier alkali‐metal sodium are much less utilised and their reactivity is less understood. Recent studies have shown the excellent potential of organosodium reagents in synthesis, finding widespread applications in cornerstone organic transformations such as deprotonative metalation, metal‐halogen exchange or Pd catalysed C−C bond formation. However, detailed procedures for the preparation of these compounds are scarce. Therefore, we report a step‐by‐step synthesis of two organosodium reagents: n BuNa and NaTMP (TMP=2, 2, 6, 6‐tetramethylpiperidide) as key building blocks in sodium organometallics, which allows the easy access to other sodiated compounds and enables chemical reactivity that is not feasible with organolithium compounds. Both can be prepared in high yields (up to 92 %), and isolated as pure solids that can be stored under argon for long periods of time (up to six months) without observed degradation. Here we further illustrate the synthetic utility of NaTMP as an efficient metalating reagent for 1‐methoxynaphthalene which can be subsequently employed in Suzuki–Miyaura couplings, as well as a precursor for sodium zincate [(TMEDA)NaZn(TMP)Et2 ], which has been obtained by co‐complexation of NaTMP, ZnEt2 and TMEDA in hexane, for which a structure has been established by X‐ray crystallography. Abstract :